Long-lines for research monitoring and efficient population regulation of an invasive apex predator, European catfish (Silurus glanis) - Vejřík, Lukáš; Vejříková, Ivana; Blabolil, Petr; Bartoň, Daniel; Sajdlová, Zuzana; Kočvara, Luboš; Peterka, Jiří; Muška, Milan; Duras, Jindřich; Jůza, Tomáš; Ribeiro, Filipe; Rivaes, Rui; et al. (Heliyon, 2024)
European catfish is a large-bodied apex predator, a key species in native areas, but invasive in others where it negatively impacts local aquatic fauna necessitates catfish regulation. However, traditional ichthyological methods face challenges in capturing it. The study presents a detailed description of the efficient long-line method, refined through 48 sampling campaigns across twelve European water bodies. This method proves cost-effective and technically undemanding, requiring an average of 5.6 bait fish to catch one European catfish per day. The long-lines outperform other techniques, with the highest Biomass per unit effort (BPUE) of 6.205 kg of catfish per man-hour and minimal by-catch (0.276 kg per man-hour). In contrast, fyke nets, the second most efficient method, achieve a BPUE of 0.621 kg of catfish per man-hour with 3.953 kg of by-catch per man-hour. To optimize long-line catches, a 15 m distance between branch lines and regular relocation is recommended. Live fish is the most effective bait with no significant differences observed among species. However, earthworms, a less controversial alternative, are also efficient, especially for smaller catfish. Our recapture approach using various ichthyological methods revealed no hook avoidance behavior by catfish after a previous catch or avoidance by a certain part of the population. The long-line method is suitable for population regulation, scientific research, and conservation efforts and is the most effective means of capturing live European catfish.
Keywords: Ichthyological method; Predation pressure; Bait; Non-native area; Large-bodied predator